The inadequacy of a magnetohydrodynamic approach to the Biermann battery. (25th January 2021) - Ridgers, C. P.; Arran, C.; Bissell, J. J.; Kingham, R. J.
Abstract : Magnetic fields can be generated in plasmas by the Biermann battery when the electric field produced by the electron pressure gradient has a curl. The commonly employed magnetohydrodynamic (MHD) model of the Biermann battery breaks down when the electron distribution function is distorted away from Maxwellian. Using both MHD and kinetic simulations of a laser-plasma interaction relevant to inertial confinement fusion we have shown that this distortion can reduce the Biermann-producing electric field by around 50%. More importantly, the use of a flux limiter in an MHD treatment to deal with the effect of the non-Maxwellian electron distribution on electron thermal transport leads to a completely unphysical prediction of the Biermann-producing electric field and so results in erroneous predictions for the generated magnetic field. This article is part of a discussion meeting issue 'Prospects for high gain inertial fusion energy (part 2)'.